2014
DOI: 10.1097/cad.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity profile of pegylated liposomal doxorubicin (Caelyx) in patients with advanced breast cancer

Abstract: Many patients with metastatic breast cancer (MBC) have been treated previously with taxanes and/or anthracyclines, which renders reinduction of anthracyclines in the palliative setting impossible because of the high cardiotoxicity of these drugs. Pegylated liposomal doxorubicin represents a means of reinducing anthracyclines without increasing cardiotoxicity. The aim of this retrospective study was to evaluate the efficacy and toxicity of Caelyx in patients with MBC. Patients with histologically confirmed MBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…This surface modification reduces clearance of nanoparticles by the cells of the RES and apparently prolongs the duration of nanoparticles remaining in circulation. 5,[7][8][9] Lipid-PEGs, especially DSPE-PEG2000, have been extensively used to prepare stealth liposomes. 7,8,10,11 Although the PEG-coating brings prolonged circulation time and enhanced accumulation at the tumor site via the EPR effect, the highly hydrophilic surface is unfavorable for the internalization of liposomes by tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This surface modification reduces clearance of nanoparticles by the cells of the RES and apparently prolongs the duration of nanoparticles remaining in circulation. 5,[7][8][9] Lipid-PEGs, especially DSPE-PEG2000, have been extensively used to prepare stealth liposomes. 7,8,10,11 Although the PEG-coating brings prolonged circulation time and enhanced accumulation at the tumor site via the EPR effect, the highly hydrophilic surface is unfavorable for the internalization of liposomes by tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9] Lipid-PEGs, especially DSPE-PEG2000, have been extensively used to prepare stealth liposomes. 7,8,10,11 Although the PEG-coating brings prolonged circulation time and enhanced accumulation at the tumor site via the EPR effect, the highly hydrophilic surface is unfavorable for the internalization of liposomes by tumor cells. 3,6,10 Thus, the anticancer efficiency of stealth liposomes containing DSPE-PEG2000 both in vitro and in vivo is far from what has been expected.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained yield was 5.9 g (91%). 1 H NMR analysis was performed in DMSO-d 6 Figure S1). The Fourier transform infrared spectroscopy (FTIR) spectrum ( Figure S2) was performed to verify the presence of the N 3 group at the reducing end.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Previous studies have indicated that doxorubicin (DOX) is very effective in breast cancer, ovarian cancer, prostate cancer, brain cancer, cervix cancer, and lung cancers. 7 However, there are still some shortcomings, including cardiac toxicity, short half-life, low solubility of aqueous solution, hindering its application. In addition, multidrug resistance (MDR) for various cancers is also an obstacle to the development of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%